Ultrasonic pulse doppler method in blood flow measurement - NOWICKI, Andrzej (Archives of Acoustics, 1977)
The phenomenon of the scattering of ultrasonic waves by the morphotic elements of blood is discussed. An analysis is presented of a correlation system for receiving Doppler signals, with consideration being given to the problem of the simultaneous measurement of the position and velocity of the blood corpuscles. The principles of operation of the device UDIMP, developed by IPPT PAN, is described and its basic technical parameters are given.